2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.27190
|View full text |Cite
|
Sign up to set email alerts
|

What Do You Want to Do with Your Life? Insights into how Engineering Students Think about their Future Career Plans

Abstract: This research paper describes findings from a qualitative analysis of engineering students' selfreported future career plans on the 2015 Engineering Majors Survey (EMS). The EMS was designed to examine current engineering students' career goals, especially surrounding innovative work, and is based in the theoretical framework of Social Cognitive Career Theory (SCCT). With the open-ended responses on the EMS, we can develop a deeper understanding of students' plans in their own words, providing insights into ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In this paper, we work with the Engineering Major Survey (EMS) longitudinal study of students' career goals by . Analysis of the contents of this study was previously conducted mainly by the social sciences with a focus on qualitative approaches to extract the most influential variables on career goals (Grau et al, 2016;Levine et al, 2017). Quantitative correlation between variables was previously explored by Atwood et al…”
Section: The Ems Study and Entrepreneurial Behavior Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we work with the Engineering Major Survey (EMS) longitudinal study of students' career goals by . Analysis of the contents of this study was previously conducted mainly by the social sciences with a focus on qualitative approaches to extract the most influential variables on career goals (Grau et al, 2016;Levine et al, 2017). Quantitative correlation between variables was previously explored by Atwood et al…”
Section: The Ems Study and Entrepreneurial Behavior Predictorsmentioning
confidence: 99%
“…Finally, the last concept is the most distinctive as it captures the plan timeline, clearly present in all the nearest neighbors listed. This concept, connecting career plans to the time dimension, cannot be found in previous works such as Grau et al (2016). The completeness scores achieved by these concepts are reported in the appendix (see C).…”
Section: Low-level Feature and Neuron Explanationsmentioning
confidence: 99%
“…In this paper, we work with the Engineering Major Survey (EMS) longitudinal study of students' career goals by . Analysis of the contents of this study was previously conducted mainly by the social sciences with a focus on qualitative approaches to extract the most influential variables on career goals (Grau et al, 2016;Levine et al, 2017). Quantitative correlation between variables was previously explored by Atwood et al (2020) relating Social Cognitive Career Theory (SCCT) (Lent et al, 1994) to different predefined topics for the purpose of survey design, such as students demographics, first-generation status, and family background.…”
Section: The Ems Study and Entrepreneurial Behavior Predictorsmentioning
confidence: 99%
“…Finally, the last concept is the most distinctive as it captures the plan timeline, clearly present in all the nearest neighbors listed. This concept, connecting career plans to the time dimension, cannot be found in previous works such as Grau et al (2016). The completeness scores achieved by these concepts are reported in the appendix (see C).…”
Section: Low-level Feature and Neuron Explanationsmentioning
confidence: 99%
“…These alumni moved between working and graduate programs, and half of the alumni reported that they were not doing what they expected for their career. Similar to the present study, another analysis explored the write-in responses at the end of a survey in which junior and senior undergraduate engineering student participants could elaborate on their career plans [11]. Together, this body of work has led to insights about the very early careers of engineering alumni (i.e., within the first five years) and overall trends in the movement of engineering alumni within the labor force.…”
Section: Background and Context Relevant Literaturementioning
confidence: 90%